Hubungan Jenis dan Lama Penggunaan Kontrasepsi Hormonal Terhadap Gangguan Menstruasi Pada Wanita Usia Subur di Puskesmas Pardamean Kecamatan Siantar Marihat Kota Pematangsiantar Tahun 2023 - Besty Agustina Silitonga; Asnita Sinaga (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Contraception is all kinds of tools or methods used by one party or both parties to avoid or prevent pregnancy (Sety, 2014). Contraceptive methods have developed with all the advantages and disadvantages of each method. Contraceptive methods can be divided into two, namely long-term contraceptive methods (Longterm Contraceptive Method), which include these methods are lUD (Intra Uterine Device) or IUD (Intrauterine Contraceptive Device), Implants, Vasectomy and Tubectomy. Meanwhile, non-long-term methods (Non-Long Contraceptive Method) include injections, pills, vaginal contraception and condoms. Apart from that, there are also natural birth control methods that follow the pregnancy cycle (Susilowati and Prasetyo, 2015). A side effect of hormonal contraception is menstrual disorders. The main side effects of DMPA (Depot Medroxyprogesteron Acetate) contraception and implants are menstrual disorders in the form of amenorrhea, spotting, changes in the cycle, frequency, length of menstruation and the amount of blood lost. The side effects of a contraceptive method are a factor that needs to be considered in determining the decision regarding the continued use of a contraceptive method (Hartanto, 2013). There were 12 respondents (70.6%) of women of childbearing age who used implant-type hormonal contraceptives who experienced menstrual disorders, the average complaint of which was the absence of menstruation for > 3 months (amenorrhea) and 5 respondents (29.4%) who not experiencing menstrual disorders. There were no 1-month injection type hormonal contraceptives who experienced menstrual disorders, while there were 4 people who were disturbed (100%). There were 13 respondents (76.5%) of the 3-month injectable type of hormonal contraception, while 4 respondents (23.5%) did not experience menstrual disorders. Of the 38 respondents who used hormonal contraception who met the requirements, they were analyzed statistically using the Chi Square test which has been carried out, the result was a p value of 0.013 (p<0.05) which indicates that there is a relationship between the type of hormonal contraception and menstrual disorders